O potencial de Ceriodaphnia cornuta Sars (1885) fa rigaudi comoorganismo-teste em estudos ecotoxicológicos: uma comparação congênere - Marcela Martins Ribeiro (2011)
The aim of this study was to essay sensivity in relation to two reference substances, sodium chloride (NaCl) and sodium dodecyl sulfate-SDS-(C12H25SO4Na) and water samples from Pampulha reservoir to Ceriodaphnia cornuta in order to evaluate its potential as test organisms in ecotoxicological studies. In addition, information on the reproduction and longevity of those species in the individual and population context was obtained. Parallel experiments were conducted using Ceriodaphnia dubia and Ceriodaphnia silvestrii, already standardized, in order to compare their responses to those of C. cornuta. The methodology used for acute toxicity essays (lethal) and chronic toxicity essays (sublethal) was described by ABNT (2003a, 2003b) respectively. In individual experiments, 8 to 10 females were kept in 20 mL of water for cultivation and monitored throughout the life cycle. In order to determine population growth, 30 females were placed in containers with 2L water, the counting of organism being carried out every other day during 15 days. The experiments were fed with Pseudokirchneriella subcapitata (2x105cel mL-1) and a 0.02 mL fish meal and yeast (RL) compound. No statistically significant differences for primipara were found among lifespan data. The average times corresponded to 3.8, 4.0, 4.1 days for C. cornuta, C. silvestrii and C. dubia, respectively. Furthermore, there were no differences compared to the number of neonates produced by primipara, with corresponding averages of 3.5, 2.6 and 2.6 neonates per female. C. cornuta, the smallest specie, presented lower average longevity, 20.6 days, while C. silvestrii and C. dubia presented 33.8 and 34.5 days, respectively. C. cornuta reproduced 34.0 neonates per female on average distributed in 6.8 litters with 4.6 neonates/brood/female throughout the lifecycle. The C. silvestrii has reproduced 111.2 neonates per female, 16.5 litters, 6.4 neonates / brood / female. For C. dubia, the average reproduction was of 100.0 neonates/female, 15.8 litters, 6.1 neonates/brood/female. The intrinsic rates of increase were 0.37, 0.31 and 0.30 for C. cornuta, C. silvestrii and C. dubia, respectively, which corresponded to densities of 9080, 4338 and 2885 individuals respectively, showing differences in C. cornuta compared to other species. The results of acute toxicity tests for both sodium chloride and for sodium dodecyl sulfate do not show statistically significant differences of sensitivity between the species in 24h and 48h. For NaCl, the respectives mean values of EC50;24h and EC50;48h for C. cornuta were 1.67 g L-1 and 1.04 g L-1; for C. silvestrii 1.97 g L-1 and 1.28 g L-1 and C. dubia 1.60 g L-1 and 1.02 g L-1. For SDS, the mean values of EC50;24h and EC50;48h correspond to 4.28 mg L-1 and 2.09 mg L-1 for C. cornuta 4.96 mg L-1 and 3.35 mg L-1, for C. silvestrii and 4.19 mg L-1 and 2.71 mg L- 1 for C. dubia. Regarding chronic toxicity tests, no differences were found between species in relation to sodium chloride with CI25 averages of 0.32, 0.37 and 0.30 g L-1 for C. cornuta, C. silvestrii and C. dubia, respectively. However, there were significant differences in relation to sodium dodecyl sulfate, with CI25 averages of 1.31, 2.32 and 2.09 mg L-1, respectively. The results of chronic toxicity tests with samples of water from the reservoir using C. cornuta as test organisms showed that it was as sensitive as C. silvestrii and C. dubia. The results of the study showed the feasibility of cultivation of C. cornuta and its potential to be used as test organisms in ecotoxicological studies